Molotov koktel - Adam Adli, 1989- (Petaling Jaya, Selangor : Orange Dove Sdn. Bhd., 2013)
Account of young student about election in university and criticism of Malaysian political government.
Koleksi Sumbangan : Dr. Syed Husin Ali
Keywords: Malaysia -- Politics and government; Adam Adli, -- 1989- -- Anecdotes